Evaluating the effect of sarconesiopsis magellanica (Diptera: Calliphoridae) larvae-derived haemolymph and fat body extracts on chronic wounds in diabetic rabbits (2015)
We evaluated extracts taken from S. magellanica third instar larvae fat body and haemolymph using a diabetic rabbit model and compared this to the effect obtained with the same substances taken from Lucilia sericata larvae. Alloxan (a toxic glucose analogue) was used to induce experimental diabetes in twelve rabbits. Dorsal wounds were made in each animal and they were infected with Staphylococcus aureus and Pseudomonas aeruginosa. They were then treated with haemolymph and lyophilized extracts taken from the selected blowflies' larvae fat bodies. Each wound was then evaluated by using rating scales and histological analysis. More favourable scores were recorded on the PUSH and WBS scales for the wounds treated with fat body derived from the larvae of both species compared to that obtained with haemolymph; however, wounds treated with the substances taken from S. magellanica had better evolution. Histological analysis revealed that treatment led to tissue proliferation and more effective neovascularisation in less time with both species' fat body extracts compared to treatment with just haemolymph. The results suggest the effectiveness of the substances evaluated and validate them in the animal model being used here as topical agents in treating chronic wounds. © 2015 Jennifher Góngora et al.